A comparative study on GaSb epilayers grown on nominal and vicinal Si(100) substrates by molecular beam epitaxy. (23rd December 2020) - Arpapay, Burcu; Suyolcu, Y Eren; Çorapç𝚤oğlu, Gülcan; van Aken, Peter A; Gülgün, Mehmet Ali; Serincan, Uğur
Abstract: The direct growth of GaSb buffer layers on Si substrates is attracting considerable interest in the integration of group III-Sb based device structures on lower-cost Si substrates. Here, we present the effect of various growth steps on the defect types and defect density that are crucial for advancing high crystal quality GaSb buffer layer on nominal/vicinal Si substrate. As a growth step, the applied thermal annealing at an intermediate step provided a decrease in the threading dislocation (TD) density down to 1.72 × 10 8 cm −2, indicating a more effective method compared to post-growth annealing. Additionally, the importance of period number and position of GaSb/AlSb superlattice layers inserted in GaSb epilayers is demonstrated. In the case of the GaSb epilayers grown on vicinal substrates, the APB density as low as 0.06 µ m −1 and TD density of 1.98 × 10 8 cm −2 were obtained for the sample grown on 4° miscut Si(100) substrate.